VALIDITAS BUKU AJAR MATA KULIAH GEOMETRI BERBASIS CAPAIAN PEMBELAJARAN - Sakur, Sakur; Saragih, Sehatta; Hutapea, Nahor Murani (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
There is a change in the competence required so that it has an impact on changes in the content and content of course material. In this regard, it is necessary to rearrange the content of the material in the course. Based on the early-end study as the Teaching Team for the Geometry course, it is deemed necessary to develop textbooks that are in line with the competency demands set to facilitate students in understanding lecture material. Researchers realize the importance of developing textbooks so that the competence of prospective teachers produced by Mathematics Education at FKIP UR is in line with the needs of Elementary and Secondary Education. The purpose of this research is to produce valid and practical textbooks used in Goemetry courses. The results of the define phase of the researcher have compiled geometry study materials, concept networks and sub-outcome indicators of course learning. This development research produced a product in the form of a Geometry textbook according to the IQF-based curriculum on flat plane geometry material in the Geometry course which has fulfilled valid aspects in terms of content validity (content according to curriculum), construct validity (according to presentation, language arrangement and appearance).